Cultural Practices & Beliefs in Abaca Farming of the Indigenous People - Salmorin, Daniel Emmanuel; Gepty, Victoria (Journal of Humanities and Social Sciences Studies, 2023)
Abaca (Musa textilis) is a plant related to the banana, the leaves of which provide one of the strongest natural fibers used by man. Abaca farming is vital in boosting the national economy, and it serves as a potential source of incomefor growers (Biccay,2016). Furthermore, the indigenous knowledge of abaca farming has been proven effective through time and experience. However, there was a scant study about indigenous knowledge on abaca farming and abaca farmers in the Province of Aklan, Philippines. The indigenous people used traditional tools, equipment and ways in phases of producing, processing and marketing abaca fiber. The processes in their production phase were the preparation of the tools, clearing and preparation of the land, preparation of plants, planting, and maintaining plant health. In the processing phase, the processes were: preparation, topping, tumbling, tuxying, extraction, drying and bundling. While in the marketing phase, the processes were: carrying fiber, meeting with the assembler and transporting fiber to the market. The cultural beliefs in abaca farming were drying of suckers, padamguhan (response of deities based on dreams), sonata sa kataeonan (music in the forest), sapat nga pihakan mata (cyclops), prohibition of cooking in the abaca field, and rituals for good luck and thanksgiving for their good harvest. The Aklanon – Bukidnon Indigenous People faced several problems and challenges in abaca farming, and because of their innate positive qualities, they made their own coping mechanisms in order to continue living and avoid delays in their work and income.